METHODOLOGICAL GUIDELINES FOR THE TRANSPROFESSIONALISM DEVELOPMENT AMONG VOCATIONAL EDUCATORS - E. F. Zeer; E. E. Symaniuk (Образование и наука)
Introduction. Nowadays, regarding the 6thwave of technological innovations and emergence of a phenomenon «transfession», there is a need for modernization of the vocational staff training in our country. Transfession is a type of the labour activity realized on the basis of synthesis and convergence of the professional competences that involve different specialized areas. Thus, the authors of the present article propose to use the professional and educational platform, developed by them, taking into account a specialists’ training specialty. The aims of the article are the following: to describe the phenomenon «transprofessionalism», to determine the initial attitudes towards its understanding; to present the block-modular model of the platform for the formation of the transprofessionalism of the teachers of the vocational school. Methodology and research methods. The research is based on the following theoretical and scientific methods: analysis, synthesis, concretization, generalization; hypothetical-deductive method; project-based method. The projecting of the transprofessionalism platform model was constructed on the basis of multidimensional, transdisciplinary, network and project approaches. Results and scientific novelty. The relevance of the discussed phenomenon in the productive-economic sphere is proved. The transprofessionalism requires a brand new content-informative and technological training of specialists. In particular, the concept «profession» has lost its original meaning as an area of the social division of labour during socio-technological development of the Russian economy. Therefore, transprofessionals are becoming more competitive and demanded in the employment market, being capable to perform a wide range of specialized types of professional activities. The structure, principles and mechanisms of the professional-educational platform functioning for transprofessionalism formation among the members of professional activities are presented. Heuristic opportunities for design of strategic academic units on the basis of transprofessionalism methodology are shown. Practical significance. The materials of the article can be useful for teachers, educators, educational supervisors and methodologists of the system of continued vocational education.